Satellite image fusion for land cover classification - Tsan, Li Ling (2017)
Land cover classification provides information on how the land has been changed over the years. Through the remote sensing techniques using Synthetic Aperture Radar(SAR), SAR images are pre-processed and later segmented to produce the segmentation maps which gives the land cover classification. To further enhance the land cover classification accuracy, the processed SAR images are fused with the optical images to form a high-resolution composite image.